The impact of COVID-19 pandemic on treatment delay and short-term neurological functional prognosis for acute ischemic stroke during the lockdown period - Gu, Shiyuan; Li, Jie; Shen, Huachao; Dai, Zhengze; Bai, Yongjie; Zhang, Shuai; Zhao, Hongyi; Zhou, Suiyun; Yu, Yan; Tang, Wuzhuang (Frontiers in Neurology, 2022)
Background Preventive strategies implemented during the COVID-19 pandemic may negatively influence the management of patients with acute ischemic stroke (AIS). Nowadays, studies have demonstrated that the pandemic has led to a delay in treatment among patients with AIS. Whether this delay contributes to meaningful short-term outcome differences warranted further exploration. Objective The objective of this study was to evaluate the impacts of the COVID-19 pandemic on treatment delay and short-term outcomes of patients with AIS treated with IVT and MT. Methods Patients admitted before (from 11/1/2019 to 1/31/2020) and during the COVID-19 pandemic (from 2/1/2020 to 3/31/2020) were screened for collecting sociodemographic data, medical history information, and symptom onset status, and comparing the effect of treatment delay. The patients treated with IVT or MT were compared for delay time and neurological outcomes. Multivariable logistic regression was used to estimate the effect of treatment delay on short-term neurological prognosis. Results In this study, 358 patients receiving IVT were included. DTN time increased from 50 min (IQR 40–75) before to 65 min (IQR 48–84), p = 0.048. 266 patients receiving MT were included. The DTP was 120 (112–148) min vs. 160 (125-199) min before and during the pandemic, p = 0.002. Patients with stroke during the pandemic had delays in treatment due to the need for additional PPE (p < 0.001), COVID-19 screening processes (p < 0.001), multidisciplinary consultation (p < 0.001), and chest CT scans (p < 0.001). Compared with pre-COVID-19, during the pandemic, patients had a higher likelihood of spontaneous intracranial hemorrhage after IVT (OR: 1.10; 95% CI, 1.03–1.30) and a lower likelihood of mRS scores 0–2 at discharge (OR: 0.90; 95% CI, 0.78–0.99). In logistic regression analysis, high NIHSS score at admission, increasing age, worse pre-admission mRS, large vessel occlusion, admission during the lockdown period, and low mTICI grade after MT were associated with an mRS ≥ 3. Conclusion The COVID-19 pandemic has had remarkable impacts on the management of AIS. The pandemic might exacerbate certain time delays and play a significant role in early adverse outcomes in patients with AIS.